Breath-hold PET/CT-guided tumour ablation under general anaesthesia: accuracy of tumour image registration and projected ablation zone overlap. Issue 3 (March 2017) - Shyn, P.B.; Tremblay-Paquet, S.; Palmer, K.; Tatli, S.; Tuncali, K.; Olubiyi, O.I.; Hata, N.; Silverman, S.G.
Abstract : Aim: To assess single-breath-hold combined positron-emission tomography/computed tomography (PET/CT) for accuracy of tumour image registration and projected ablation volume overlap in patients undergoing percutaneous PET/CT-guided tumour-ablation procedures under general anaesthesia. Materials and methods: Eight patients underwent 12 PET/CT-guided tumour-ablation procedures to treat 20 tumours in the lung, liver, or adrenal gland. Using breath-hold PET/CT, the centre of the tumour was marked on each PET and CT acquisition by four readers to assess two- (2D) and three-dimensional (3D) spatial misregistration. Overlap of PET and CT projected ablation volumes were compared using the Dice similarity coefficient (DSC). Interobserver differences were assessed with repeated measure analysis of variance (ANOVA). Technical success and local progression rates were noted. Results: Mean tumour 2D PET/CT misregistrations were 1.02 mm (range 0.01–5.02), 1.89 (0.03–7.85), and 3.05 (0–10) in the x, y, and z planes. Mean 3D misregistration was 4.4 mm (0.36–10.74). Mean projected PET/CT ablation volume DSC was 0.72 (±0.19). No significant interobserver differences in 3D misregistration ( p =0.73) or DSC ( p =0.54) were observed. Technical success of ablations was 100%; one (5.3%) of 19 tumours progressed. Conclusion: Accurate spatial registration of tumours and substantial overlap of projected ablation volumes are achievable when comparing PET and CT acquisitions from single-breath-hold PET/CT. The results suggest that tumours visible only at PET could be accurately targeted and ablated using this technique. Highlights: Breath-hold PET/CT scans are feasible during tumour ablations performed with general anesthesia. Breath-hold PET/CT minimizes image misregistration effects on tumour targeting/planning. Tumours visible only on PET could potentially be successfully ablated using breath-hold PET/CT.